Pre-Service English Teachers' Goals and Beliefs in the Indonesian PPG Program - Attabik, Muhammad Haikal; Zainiza, Mailiza (Language Circle: Journal of Language and Literature, 2025)
This study investigates the professional goals and beliefs of pre-service English teachers participating in Indonesia’s Teacher Professional Education (PPG) Program, a pivotal initiative designed to strengthen teacher competence and identity. While prior studies have focused on policy and structural aspects of the PPG, little is known about how pre-service teachers internalize professional goals and beliefs within this program’s reflective learning context. Addressing this gap, the present study adopts a small-scale exploratory case study involving three pre-service English teachers at a state university in West Java. Data were collected through semi-structured interviews and analyzed using Miles, Huberman, and Saldaña’s (2014) framework to derive thematic insights into participants’ motivational orientations and evolving professional beliefs. Findings reveal that participants’ motivations combined intrinsic ideals such as pedagogical growth and moral purpose with extrinsic considerations of certification and career advancement. Their professional goals shifted from self-improvement toward broader commitments to educational transformation, while beliefs about English teaching expanded from linguistic transmission to global competence facilitation. These findings underscore that professional identity in the PPG context develops through the interaction of motivational and belief systems shaped by both policy expectations and personal reflection. The study contributes to teacher education research by providing contextualized, in-depth insights into how pre-service English teachers in Indonesia construct professional identity amid systemic reforms. Implications are offered for designing PPG curricula that explicitly integrate goal-setting, belief development, and reflective mentorship.